Sosialisasi Dan Edukasi Green Human Resource Management Pada Pegawai Dinas Perindustrian Sumatera Selatan - Apriyanza, Muhammad; Mellita, Dina; Fitriasuri, Fitriasuri; Elpanso, Efan; Noviardy, Andrian (Pakis Journal Institute, 2025)
The development Over time, human resource management has changed, one which is the creation of ecologically friendly company activities by producing the concept of Green Human Resources Management (GHRM). Currently, Green Human Resource Management has become the main business strategy for substantial organizations where Human Resource Development has an active role in the work environment. Green resource management is a policies for environmentally conscious companies resource management Management is human resources that are aware of scientific disciplines aware of scientific disciplines by combining with maintain the sustainability of nature in company management. Green Human Resource Management is a program that helps create a green workforce that can understand and appreciate green culture in an organization that requires high-level technical and management skills in employees. Green Human Resource Management practices in supporting better environmental performance. The approach is a qualitative one that is based on empirical research by examining use in empirical research by examining use green human resources management in the industrial world based on” devotion results from various parties, with sources of national journals, international journals.